2018
DOI: 10.1111/head.13272
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Neurologists on Postconcussion Syndrome

Abstract: The majority of respondents agree with the following: PCS is a clearly defined syndrome with a solid basis for determining prognosis with an organic basis; accept the authenticity of patients' reports of symptoms; effective treatment is available for headaches lasting 3 months or more; headaches persist in over 20% 1 year after injury; and cognitive rehabilitation is effective. The majority of the respondents do not agree with the following: symptoms improve in a relatively short period of time and quickly res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The duration of post‐traumatic amnesia may not be accurate. Causes for inaccurate durations include the following: psychogenic amnesia (due to an acute stress disorder or PTSD); the effect of alcohol or drugs (either taken by the patient or administered by paramedics or physicians); and other physical injuries and pain 5 …”
Section: Expert Opinionmentioning
confidence: 99%
See 1 more Smart Citation
“…The duration of post‐traumatic amnesia may not be accurate. Causes for inaccurate durations include the following: psychogenic amnesia (due to an acute stress disorder or PTSD); the effect of alcohol or drugs (either taken by the patient or administered by paramedics or physicians); and other physical injuries and pain 5 …”
Section: Expert Opinionmentioning
confidence: 99%
“…In 1674, Boirel suggested that invisible brain damage might occur in concussion 3 . Concussion has been a controversial medico‐legal topic for over 150 years 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…Three studies in civilians, which involved either monotherapy or combined therapy with propranolol, amitriptyline, or valproate, showed efficacy, although a small study showed no benefit with amitriptyline . In a survey of neurologists, 57% agree that “effective treatment is available for headaches lasting 3 months or more.”…”
Section: Expert Opinionmentioning
confidence: 99%